2011
DOI: 10.3109/10242422.2011.638057
|View full text |Cite
|
Sign up to set email alerts
|

Lipase-catalyzed synthesis of poly(ε-caprolactone) and characterization of its solid-state properties

Abstract: Ring-opening polymerization of ε-caprolactone has been successfully conducted using an immobilized form of Candida antarctica lipase B as catalyst. The effects of enzyme concentration, reaction medium, reaction temperature and time on monomer conversion and product molecular weight were investigated. Through optimization of reaction conditions, poly( ε -caprolactone) (PCL) was obtained with 99% monomer conversion and a number-average molecular weight ( M n ) of 18870 g/mol. The reaction system was then scaled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
3
3
0
Order By: Relevance
“…In particular, the ROP reaction conducted in toluene (1:2 wt/vol, substrate/toluene ratio) at 70 °C for 4 h afforded 85% monomer conversion and M n 17 000 g mL ‐1 (PDI 1.8); the scaling up from 0.3 mL ϵ‐caprolactone to 10 mL even increased M n to 44 800 g mL ‐1 (PDI 1.7) while the isolated yield (86%) remained high. Similar results were reported by the Li group that more hydrophobic solvents (such as toluene, cyclohexane and n ‐hexane) led to high M n (up to ∼18 900 g mol ‐1 ) of poly(ϵ‐caprolactone) from the enzymatic ROP catalyzed by Novozym 435, while less hydrophobic ones (e.g. 1,4‐dioxane, acetone, THF, and chloroform) yielded lower molecular weights (2800–4200 g mol ‐1 ).…”
Section: Enzymatic Rop In Organic Solventssupporting
confidence: 85%
“…In particular, the ROP reaction conducted in toluene (1:2 wt/vol, substrate/toluene ratio) at 70 °C for 4 h afforded 85% monomer conversion and M n 17 000 g mL ‐1 (PDI 1.8); the scaling up from 0.3 mL ϵ‐caprolactone to 10 mL even increased M n to 44 800 g mL ‐1 (PDI 1.7) while the isolated yield (86%) remained high. Similar results were reported by the Li group that more hydrophobic solvents (such as toluene, cyclohexane and n ‐hexane) led to high M n (up to ∼18 900 g mol ‐1 ) of poly(ϵ‐caprolactone) from the enzymatic ROP catalyzed by Novozym 435, while less hydrophobic ones (e.g. 1,4‐dioxane, acetone, THF, and chloroform) yielded lower molecular weights (2800–4200 g mol ‐1 ).…”
Section: Enzymatic Rop In Organic Solventssupporting
confidence: 85%
“…Sasi et al reported different results for cyclic and linear solvent molecules and cyclohexane resulted in better yields than linear n‐hexanes, even though the latter possesses higher log P value . Similar results were obtained by Yang et al for the polymerization of ε‐CL . Lactonizations showed higher yields in isooctane than in octane although their log P values are nearly the same .…”
Section: Lactonization and Ring‐opening Polymerizationsupporting
confidence: 53%
“…In toluene, the highest molecular weights were obtained at 40 °C, which is in accordance with the findings of Yang et al where 45 °C reaction temperature yielded higher molecular weights than 60 °C. Increasing reaction time from 24 to 48 h led to a considerable decrease in molecular weight, probably due to more predominant hydrolysis and transesterification reactions after all cyclic monomers were consumed . When PEG was used as a macroinitiator in the eROP of ε‐CL in toluene, the temperature of 80 °C yielded significantly higher conversions and molecular weights than 60 °C.…”
Section: Lactonization and Ring‐opening Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all polymerization reactions were conducted in organic solvents, such as: toluene [40], 1,4-dioxane [41], isopropyl ether [42], isooctane [43], diphenyl ether [44], cyclohexane [45]. The reaction was also carried out in supercritical carbon dioxide [46,47], ionic liquids [48][49][50], and recently, in aqueous dispersion [51].…”
Section: Linear and Star Ester Oligomersmentioning
confidence: 99%